1995
DOI: 10.3177/jnsv.41.485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Platycodon Grandiflorum Feeding on Serum and Liver Lipid Concentrations in Rats with Diet-Induced Hyperlipidemia.

Abstract: SummaryTo study the effect of Platycodon grandiflorum (P. g.) feed ing on serum and liver lipid concentrations, diet-induced hyperlipidemic rats were fed diets containing 5% and 10% P. g, powder for 3 weeks. The P. g. feeding markedly decreased both serum and liver lipid concentrations in hyperlipidemic rats. Especially, 5% P. g. diet significantly decreased the concentrations of total cholesterol and triglycerides in serum and liver as compared with those of the hyperlipidemic control group. Dietary P. g. als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…Some evidence shows that Platycodi radix extracts possess some health benefits such as the improvement of hypercholesterolemia and hyperlipidemia. 78 The saponin-rich fraction of Platycodi radix has an inhibitory effect on HPL and this seems to correlate with anti-obesity actions. [79][80][81][82] Among the various saponins, platycodin D possesses the strongest HPL inhibitory activity with a Ki of 0.18 mM.…”
Section: Platycodin Saponinsmentioning
confidence: 99%
“…Some evidence shows that Platycodi radix extracts possess some health benefits such as the improvement of hypercholesterolemia and hyperlipidemia. 78 The saponin-rich fraction of Platycodi radix has an inhibitory effect on HPL and this seems to correlate with anti-obesity actions. [79][80][81][82] Among the various saponins, platycodin D possesses the strongest HPL inhibitory activity with a Ki of 0.18 mM.…”
Section: Platycodin Saponinsmentioning
confidence: 99%
“…However, the present study, platycodon saponin content from several samples showed that the wild roots of platycodon contained 7.3-11.8% saponins; cultivated roots had 1.7-14% saponins 15 . Whereas the level of crude saponins in platycodon was said to be 2% in a medicinal grade material in Korea reported by Kim et al, 1995 etc 16 . In Korea, it is noted that the content of saponins varies with respect to the climatic condition than in China.…”
Section: Platyconic Acidmentioning
confidence: 99%
“…The content of 4 major saponins varied largely among different growing times indicates that climatic and edaphic factors are directly involved for saponin content. The variation of saponin content varied with reagions, environmental conditions were reported by several investigation [15][16][17][18] . Those findings are directly coincided with our findings.…”
Section: Platyconic Acidmentioning
confidence: 99%
“…On the basis of fingerprint analysis of BC703, it contained a large group of oleanane-type triterpenoid saponins, such as deapioplatycoside E, platycoside E, platycodinD 3 (Fig. 1).…”
Section: Hplc-elsd Fingerprint-analysismentioning
confidence: 99%
“…It was reported to contain a lot of carbohydrates (at least 90%), protein (2.4%), lipids (0.1%) and ash (1.5%) ( 1 ). Recently, it has been reported that the polysaccharides isolated from the root of Platycodon grandiflorum prevent obesity, hypecholesterolemia, hypertension, diabetes, immune modulation and hyperlipidemia (2)(3)(4)(5). In addition, triterpenoid saponins in the roots of the Platycodon grandiflorum are believed to prevent chemical-induced hepatotoxicity ( 6,7 ).…”
mentioning
confidence: 99%